Ethnobiological Study of Kawung Motif to Promote Knowledge of Batik Through Educational Video Production - Salwa Zainum Muttaqin; Priscilia Talabessy; Alexis Rachel Maria Rosauli Napitupulu; Fajar Adinugraha (Borneo Journal of Biology Education (BJBE), 2025)
There has been a decline in the knowledge of batik among younger generations, including its meaning and underlying philosophy. Knowledge of batik may be cultivated by creating educational videos incorporating ethnobiological studies. No studies have been conducted on kawung batik in educational video production. This research aims to examine batik kawung from an ethnobiological perspective and create an educational video to facilitate Knowledge of batik instruction. The research method is exploratory and qualitative. The research methodology employed various techniques, including interviews, document analysis, and a review of relevant literature. The findings indicated that the kawung batik motif was derived from the geometrical arrangement of kolang-kaling. This batik will reflect the meanings of purity, perfection, and completeness. The tools and materials utilized remain traditional, with a 12-step manufacturing process. Five species are associated with the production of kawung batik, which are classified into eudicots and monocots. The study's findings on kawung batik have been transformed into an educational video to impart Knowledge of batik. Knowledge of batik has the potential to facilitate the simultaneous teaching of local wisdom, indigenous knowledge, and biodiversity.